Federalism and Intergovernmental Financial Relations in Canada - Jones, Allan Thomas (My University, 1969)
This thesis is concerned with the development and evolution of intergovernmental financial relations from the time of Confederation to the present day. The particular area of interest is the time from 1946 to 1968. The past quarter century has seen a powerful resurgence in provincial influence and in-creasing demands from the provinces for financial autonomy. The provincial revenues have been very much increased, but so too have their responsibilities. As Federal Government revenues have increased much more rapidly than Federal responsibilities the period has also been marked by considerable increases in payments from the Federal to the Provincial Governments. It is around the conditions attached to these increased payments that the majority of Federal-Provincial conflicts have been concentrated. The increasing degree of variation in economic wealth seen between the provinces, the increasing degree of urbanization, and the rapid growth of provincial revenues, will all be considered. Possible solutions to the more serious and immediate problems are considered but no 'grand solution' is offered since it seems unlikely that any static solution could hope to satisfy the needs in a society as dynamic as Canada is, and will continue to be, for the remainder of this century.
Keywords: Political Science; Political Science